Volume 6: Turbo Expo 2005, Parts a and B 2005
DOI: 10.1115/gt2005-68541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maximum Camber Location on Aerodynamics Performance of Transonic Compressor Blades

Abstract: It is well known that to increase rotational velocity is one of the effective measures to increase total pressure ratio. With increasing velocity, under the condition of transonic flow, the obvious effect of maximum camber location on aerodynamics performance of compressor blades especially in the supersonics zone can be found. In order to reduce the blade losses and to improve the blade design methodology it is necessary to study this complex flow mechanism. This paper describes only the influence of relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Fan blade was optimized by Idahosa et al [12] through an automated optimization procedure. Effect of maximum camber location on a transonic compressor blade was reported by Chen et al [13]. They studied numerically and suggested that efficiency can be increased changing the airfoil shape.…”
Section: Introductionmentioning
confidence: 91%
“…Fan blade was optimized by Idahosa et al [12] through an automated optimization procedure. Effect of maximum camber location on a transonic compressor blade was reported by Chen et al [13]. They studied numerically and suggested that efficiency can be increased changing the airfoil shape.…”
Section: Introductionmentioning
confidence: 91%
“…Several other studies on shape optimization of turbomachinery blades have been undertaken, with specific emphases on maximum camber [7], camber line [8][9], airfoil thickness [10], thickness location [11], trailing edge (TE) radius [12], and others.…”
Section: Introductionmentioning
confidence: 99%
“…Oyama et al [63] reported blade profile modification with the help of B-spline curve of NASA rotor 67 to increase adiabatic efficiency by 2%. Chen et al [69] optimized camber line, thickness distribution and stacking line by polynomial curve to define compressor blade and gained 1.73% improvement of adiabatic efficiency. Maximum camber location effect was studied by Chen et al [69].…”
Section: Applications Of Surrogate Based Optimization Methodsmentioning
confidence: 99%
“…Chen et al [69] optimized camber line, thickness distribution and stacking line by polynomial curve to define compressor blade and gained 1.73% improvement of adiabatic efficiency. Maximum camber location effect was studied by Chen et al [69]. Benini [53] defined blade section profiles by Bezier curve using multi-objective optimization considering total pressure ratio and adiabatic efficiency as objectives for design of a compressor blade.…”
Section: Applications Of Surrogate Based Optimization Methodsmentioning
confidence: 99%